Polycystic ovary syndrome and its impact on Iranian women's quality of life: a population-based study - Zahra Behboodi Moghadam; Bita Fereidooni; Mohsen Saffari; Ali Montazeri (BMC, 2018)
Abstract Background Polycystic ovary syndrome (PCOS) is a major public health concern worldwide affecting up to one in five women at reproductive age. It is associated with biochemical and hormonal disturbances as well as adverse cosmetic, reproductive, metabolic, and psychological consequences, resulting in worsened quality of life. The aim of the present study is evaluating the quality of life and determining its degrading factors among Iranian women suffering from this syndrome. Methods This cross-sectional study was conducted on 200 PCOS women in Hamadan, Iran. In order to measure quality of life we used the Persian version of Health-related Quality of Life Questionnaire for PCOS (PCOSQ). Descriptive statistics was used to explore the data. In addition linear regression analysis was performed to assess factors affecting health-related quality of life in this population. Results The mean score for quality of life domains (from the greatest to the least serious concern) were: infertility (3.43 ± 1.63), emotions (3.55 ± 1.17), menstrual problems (3.77 ± 1.36), body hair (3.80 ± 2.05) and weight (4.32 ± 1.80), respectively. The higher score represents better function. However, multivariate analysis revealed that hirsutism had the strongest impact on the patients' quality of life (p < 0.001) followed by infertility (p = 0.038) and menstrual irregularity (p = 0.003). Conclusion The findings showed that impairment of quality of life was associated with PCOS related conditions such as hirsutism, infertility and menstrual problems.